Harmonizacja i standaryzacja zasad rachunku kosztów łączonych spółek - Szydełko, Alfred (Harmonization and Standarization of Costs Account's Principles of the Joint Partnerships, 2006)
The settlement of the mergers in the capital partnerships can be done by the use of the method of acquisition and by joining the shares. Each method determines certain integration consequences for the cost account systems of the mergered partnerships. The integration of such accounts tries to unify the rules of the cost account and the responsibility is taken by the management of the joint partnerships.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 364-368